South-Indian horizons: felicitation volume for François Gros on the occasion of his 70th birthday - Chevillard, Jean-Luc; Wilden, Eva (Institut Français de Pondichéry, 2004)
This volume, a tribute to François Gros and a celebration of the field of Tamil studies, demonstrates the international nature of this area and its wide range of topics. The contributors stem from sixteen different countries. They are literary historians and critics, philologists, linguists, cultural anthropologists, political and social historians, archaeologists, epigraphists, numismatists, art and architecture historians, some of them assuming two of these guises, and some having an interest in related languages: Irula, Kannada, Malayalam and Telugu. However there is much linkage and this "connexité dans la diversité" binds the different contributions together. François Gros has been the principal standard-bearer for Tamil studies in France. He has also devoted himself to the re-establishment of the École Française d'Extrême-Orient in countries of Southeast Asia. Among his other responsibilities has been the directorship for Tamil studies at the Institut Français in Pondicherry
Keywords: Aufsatzsammlung; Festschrift; Kultur; Geschichte; Indien; Drawidische Sprachen; Sprache; Literatur; Tamil